Preoperative Imaging Assessment and Staging of Perihilar Cholangiocarcinoma: Tips and Pitfalls - Yu Shan Stephanie Yong; Zhuyi Rebekah Lee; Yock Teck Nicholas Soh; Su Chong Albert Low (Journal of the Korean Society of Radiology)
This article outlines the systematic radiological approach preoperative evaluation of perihilar cholangiocarcinoma (pCCA) using CT and MRI to provide key information regarding the suitability for curative surgical resection. It discusses older classification systems (Bismuth- Corlette, Memorial Sloan Kettering Cancer Center T staging) and follows the Korean Society of Abdominal Radiology 2019 consensus recommendations for step-by-step assessment. The correlation between radiological, surgical, and pathological findings is illustrated through a pictorial review of pathologically proven cases. Benign and malignant mimics of pCCA are included to provide a comprehensive overview.